Population Genomics Reveals Demographic History and Genomic Differentiation of Populus davidiana and Populus tremula - Hou, Zhe; Li, Ang (Frontiers in Plant Science, 2020)
Abstract: Forest trees are an excellent resource from which to understand speciation and heterogeneous genome variation patterns due to the majority of forest trees being distributed widely and able to adapt to different climates and environments. Populus davidiana and P. tremula are among the most geographically widespread and ecologically important tree species in Northern Hemisphere. Whole-genome resequencing data of 50 individual examples of P. davidiana and P. tremula throughout Eurasia was conducted, finding that genetic differentiation was evident between the two species, the FST values between P. davidiana and P. tremula was 0.3625. The ancestors of the two aspen diverged into P. davidiana and P. tremula species approximately 3.60 million years ago (Mya), which was in accordance with the rapid uplift of Qinghai-Tibet Plateau (QTP) around the Miocene/Pliocene boundary. The two species experienced a considerable long-term bottleneck after divergence, with population expansion beginning approximately 20,000 years years ago after the end of the last glacial maximum. Although the majority of regions of genomic differentiation between the two species can be explained by neutral processes, some outlier regions have also been tested that are significantly influenced by natural selection. We found that the highly differentiated regions of the two species exhibited significant positive selection characteristics, and also identified long-term balancing selection in the poorly differentiated regions in both species. Our results highlight that linked selection and rates of recombination were important factors in genomic differentiation between the the two aspen species. Given the modern-day geographic isolation, disjunct distribution and extremely low rates of gene flow, our results support an allopatric model of speciation for these two aspen species.